Firms' attributes determining auditors' remuneration: empirical evidence from Nigeria. (2015) - Asien, Etumudon Ndidi
There is scant evidence from developing economies on firms' attributes that determine auditors' remuneration. This paper investigates the relationship between auditors' remuneration and number of audit committee meetings, clients' familiarity, complexity, financial risk and age. Using data from 2010-2011 annual reports and financial statements of 70 quoted firms on the Nigerian Stock Exchange, the paper tests five hypotheses using multivariate techniques. The findings suggest that auditors' remuneration is positively significantly related to number of audit committee meetings, complexity, and financial risk whereas auditors' remuneration is inversely significantly related to familiarity. The finding indicates that there is no significant relationship between age and auditors' remuneration. Based on the findings, the paper recommends that firms should hold audit committee meetings only when necessary because external auditors build costs of attending meetings into their prices; and that firms should engage external auditors for more than one consecutive time because familiarity reduces auditors' remuneration.